Konflik Sosial dalam Kumpulan Cerpen “Kembali ke Pangkal Jalan” Karya Yusrizal K.W. - Harahap, Holijah; Amrizal, Amrizal; Hiasa, Fina (UNIB Press, 2025)
The purpose of this study is to find out what forms of social classes occur from the collection of short stories through behavior, attitudes of characters in the collection of short stories